Macrofauna abundance and diversity patterns of deep sea southwestern Gulf of Mexico - Quintanar-Retama, Octavio; Vázquez-Bader, Ana Rosa; Gracia, Adolfo (Frontiers in Marine Science, 2023)
The diversity and distribution of macrofaunal communities in the deep-sea bottoms of Gulf of Mexico (GoM) Mexican waters are poorly known compared to the northern GoM. This study was designed to contribute to the knowledge of macrofauna communities through (i) evaluate the taxonomic composition of macrofauna communities at major taxa level, and (ii) analyze the spatial distribution patterns in the deep sea of the southwestern GoM. Benthic macrofauna composition was analyzed in a large geographical area (92.67°–96.70° W 18.74°–23.04° N) and bathymetric gradient (185-3740 m depth). Samples were collected on board the R/V Justo Sierra (Universidad Nacional Autónoma de México) with a Reineck-type box corer during the oceanographic cruises SOGOM-3 and SOGOM-4 carried out on April 21–May 15, 2017, and on August 29–September 20, 2018, respectively. Thirteen environmental parameters were measured (among them, depth, salinity, temperature, O2, sediment grain size, hydrocarbons, and organic matter). Twenty-five taxa were registered in SOGOM 3 (2315 individuals) all of which were observed in SOGOM 4 (1721 individuals) with exception of the mollusk Class Solenogastres. The average abundance (ind. m-2) registered was 517 (range: 150-1388 ind. m-2), and 347 (range: 38-1088 ind. m-2) for SOGOM 3, and SOGOM 4, respectively. In SOGOM 3 Polychaeta, Nematoda, Amphipoda, Tanaidacea, and Bivalvia contributed with 75% of the total abundance, which were also the most abundant in SOGOM 4 representing 82% of total macrofauna abundance. Highest abundance was registered to the south of the study area near the coast, and the lowest one was found in deeper areas. Macrofauna abundance decreased with depth in both cruises. High diversity values were registered at intermediate depths in the south and west zones of the study area. Both cruises separated in a nMDS analysis. During SOGOM 3 dissolved oxygen, aromatic hydrocarbons, and organic matter (%) were the environmental variables related to macrofauna whereas, in SOGOM 4, depth was the most important one. This study fills a gap in the knowledge of diversity and distribution of macrofaunal communities of the deep-sea bottoms of a large area covering the whole bathymetric range of southern Gulf of Mexico and provides a baseline useful to compare with polluted areas and for assessing the impact of chronic pollution and/or potential oil spill accidents.